Public Participation in Healthy City Planning: Maintaining a Balanced Usage of City Green Spaces - Diki Suherman (International Journal of Nusantara Islam, 2022)
The rapid development of urbanization has made cities experience an increase in urban population from rural areas who are looking for and creating new livelihoods. This urbanization is an opportunity for the city to develop the city through aspects of development that support the economic growth of the city. However, this aspect of urban development also has an impact on the use of less and less green openspace, this is of course a new problem in the use of public space, such as parks planted with oxygen-producing plants, because humans cannot be separated from healthy air, this is influenced by the amount of oxygen produced from plants around the city. For this reason, the purpose of writing this is to explain public participation in planning a healthy city, a perfect balance of the use of urban green space. The method used is a literature study by reviewing and examining literature related to public participation and healthy cities, especially the use of green spaces. In this paper, we will discuss the theoretical and empirical debates about the role of public participation in planning healthy cities, which is seen from the balance of green openspace as a public space which is very important for human health in the city where it lives, because public participation needs to be carried out bottom-up by building collaborative participation, involving citizens as subjects who play an active role directly.